Gullah Geechee home cooking : recipes from the matriarch of Edisto Island - Meggett, Emily; Stewart, Kayla; Michelle, Trelani (Abrams, 2022)
"The first major Gullah Geechee cookbook from "the matriarch of Edisto Island," who provides delicious recipes and the history of an overlooked American community. The history of the Gullah and Geechee people stretches back centuries, when enslaved members of this community were historically isolated from the rest of the South because of their location on the Sea Islands of coastal South Carolina and Georgia. Today, this Lowcountry community represents the most direct living link to the traditional culture, language, and foodways of their West African ancestors."--Amazon.